Hydrogeochemistry of Epikarst Spring During Rainy Seasons in the Ponjong Hydrogeological Subsystem, Gunungsewu Karst Area, Indonesia - Kurniatillah, Aulia Nisa (EDP Sciences, 2023)
Gedaren Spring is an important source of clean water and irrigation water that is located in the transition zone between the Gunungsewu Karst and the Wonosari Basin. Limestone dissolution is the dominant process influencing this epikarst spring’s dynamics, but there has been no temporal hydrogeological testing on its ion content. This hydrogeochemical study was intended to determine the characteristics and quality of Gedaren Spring water during the rainy season. The methods used in the chemical analysis were Schoeller, Piper, and chemographic diagrams, and the results were correlated with spring discharge measurements and rainfall. The chemical analysis showed a positive correlation between discharge and rain, the temporal presence of dominant ions, and temporal correlation patterns between variables. Ca2+ and HCO3- were the dominant cation and anion. The spring water was classified as calcium-enriched, calcium, bicarbonate, Ca2+ + Mg2+, and HCO3--type groundwater and as unpolluted groundwater, suggesting good water quality. Chemographic patterns indicated that Mg2+, Cl-, and SO42- ions positively correlated with discharge and rainfall, while Ca2+, HCO3-, Na+, K+, pH, EC, temperature, and TDS negatively correlated with the two variables. Overall, Gedaren Spring has good chemical characteristics and quality during the rainy season has a dominant process of calcium enrichment and is of the type Ca2++Mg2+ and HCO3- © 2023 EDP Sciences. All rights reserved.